61.24.14 problem 14

Internal problem ID [12427]
Book : Handbook of exact solutions for ordinary differential equations. By Polyanin and Zaitsev. Second edition
Section : Chapter 1, section 1.3. Abel Equations of the Second Kind. subsection 1.3.3-2.
Problem number : 14
Date solved : Tuesday, January 28, 2025 at 03:01:40 AM
CAS classification : [[_Abel, `2nd type`, `class A`]]

\begin{align*} y^{\prime } y&=\left (a \left (n -1\right ) x +b \left (2 \lambda +n \right )\right ) x^{\lambda -1} \left (a x +b \right )^{-\lambda -2} y-\left (a n x +b \left (\lambda +n \right )\right ) x^{2 \lambda -1} \left (a x +b \right )^{-2 \lambda -3} \end{align*}

Solution by Maple

dsolve(y(x)*diff(y(x),x)=(a*(n-1)*x+b*(2*lambda+n))*x^(lambda-1)*(a*x+b)^(-lambda-2)*y(x)-(a*n*x+b*(lambda+n))*x^(2*lambda-1)*(a*x+b)^(-2*lambda-3),y(x), singsol=all)
 
\[ \text {No solution found} \]

Solution by Mathematica

Time used: 0.000 (sec). Leaf size: 0

DSolve[y[x]*D[y[x],x]==(a*(n-1)*x+b*(2*\[Lambda]+n))*x^(\[Lambda]-1)*(a*x+b)^(-\[Lambda]-2)*y[x]-(a*n*x+b*(\[Lambda]+n))*x^(2*\[Lambda]-1)*(a*x+b)^(-2*\[Lambda]-3),y[x],x,IncludeSingularSolutions -> True]
 

Not solved